Extraction socket preservation - Kim, Young-Kyun (J Korean Assoc Oral Maxillofac Surg, 2020)
Extraction socket preservation (ESP) is widely performed after tooth extraction for future implant placement. For successful outcome of implants after extractions, clinicians should be acquainted with the principles and indications of ESP. It is recommended that ESP be actively implemented in cases of esthetic areas, severe bone defects, and delayed implant placement. Dental implant placement is recommended at least 4 months after ESP.